2021
DOI: 10.1002/chem.202100949
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of π‐Backbonding for the Reactivity of Electrophilic Anions [B12X11] (X=F, Cl, Br, I, CN)

Abstract: Electrophilic anions of type [B 12 X 11 ] À posses a vacant positive boron binding site within the anion. In a comparatitve experimental and theoretical study, the reactivity of [B 12 X 11 ] À with X=F, Cl, Br, I, CN is characterized towards different nucleophiles: (i) noble gases (NGs) as σ-donors and (ii) CO/N 2 as σ-donor-π-acceptors. Temperature-dependent formation of [B 12 X 11 NG] À indicates the enthalpy order (X=CN) > (X=Cl) � (X=Br) > (X=I) � (X=F) almost independent of the NG in good agreement with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 57 publications
4
29
0
3
Order By: Relevance
“…Finally, the case of X = F is characterized by a substantially stronger orbital interaction with H 2 . This is unlike what has been observed for the attraction of noble gas atoms, which is weakest for X = F. This striking difference is in line with results from a recent publication, 43 which compared the binding of noble gases, N 2 and CO at B 12 X 11 − . It was found that X = F shows the weakest binding of noble gas atoms but the strongest binding of N 2 and CO due to π-like backbonding from B 0 into the antibonding σ* orbitals of the attached molecule (something which is not possible for noble gases).…”
Section: Resultssupporting
confidence: 85%
“…Finally, the case of X = F is characterized by a substantially stronger orbital interaction with H 2 . This is unlike what has been observed for the attraction of noble gas atoms, which is weakest for X = F. This striking difference is in line with results from a recent publication, 43 which compared the binding of noble gases, N 2 and CO at B 12 X 11 − . It was found that X = F shows the weakest binding of noble gas atoms but the strongest binding of N 2 and CO due to π-like backbonding from B 0 into the antibonding σ* orbitals of the attached molecule (something which is not possible for noble gases).…”
Section: Resultssupporting
confidence: 85%
“…The large ratio of covalent interaction in these heavier Ng-containing compounds in Table 3 demonstrates that ] À is often regarded as σ donor-acceptor interaction. [27] The deformation density is used to visualize the charge transfer between two fragments. Figure S4 shows the deformation density with the largest contribution of dative bond and electron-sharing bond for [B 12 (OBO) 11 ] À and Ar.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a systematical study on the reactivity of [B 12 X 11 ] À (X = F, Cl, Br, I, CN) towards Ngs were carried out and the results show that Ngindependent reactivity trend follows the sequence: CN 11 ] À . [27] The reactivity of those monoanions towards Ngs can be attributed to bindingsite boron atom in [B 12 X 11 ] À and steric effects. [B 12 (BO) 12 ] 2À has been studied theoretically with a second electron binding energy of 5.89 eV, which is even higher than that of [B 12 (CN) 12 ] 2À (ca.…”
Section: Introductionmentioning
confidence: 99%
“…The optimized geometries of [B 12 We should point out that Mayer et al 25 had studied the interaction of CO and N 2 with [B 12 X 11 ] − (X = F, Cl, Br, I, and CN) both experimentally and theoretically. The binding of N 2 with [B 12 F 11 ] − , namely 1.73 eV, is slightly larger than that to [B 12 (CN) 11 ] − , namely 1.71 eV.…”
mentioning
confidence: 99%